ANGULAR CHEILITIS PATIENTS PROFILES AND DEMOGRAPHIC DATA AT FKG USU DENTAL HOSPITAL IN 2016: DATA DEMOGRAFI DAN PROFIL PENDERITA ANGULAR CHEILITIS DI RUMAH SAKIT GIGI MULUT FKG USU TAHUN 2016 - Serelady, Serelady; Wilda H. Lubis (Dentika: Dental Journal, 2016)
Angular cheilitis (AC), an inflammation characterized by fissure lesion at corner of the mouth that extends to the skin referred to as mucocutaneous junction region. Subjective complaints from the potential patients such as pain when eating, talking, and also when cleaning oral cavity. The aim of this study was to know the profile and demographic data of angular cheilitis patients at Rumah Sakit Gigi dan Mulut Fakultas Kedokteran Gigi in 2016. The primary data was obtained from 159 medical records, which is the total sampling. The data collected consists of age, gender, BMI (Body Mass Index), oral hygiene, distribution of lesions and healing period. The results showed that distribution and frequency of angular cheilitis most commonly found in the age range 5-14 (88,7%), male gender (56,6%), BMI with underweight category (79,9%), oral hygiene with moderate category (58,5%), the most frequent distribution of lesions bilaterally (72,3%) and the healing time is more than 7 days (58%). It can be concluded that angular cheilitis can occur among children age group, with poor nutritional status and bad oral hygiene condition. This information is expected to be an input to the government that clinical descriptions of angular cheilitis in children, with BMI underweight, were clues to improve children’s nutritional status and it is required to make a comprehensive improvement to nutritional status and oral hygiene.